The Trail of Tears - Bruchac, Joseph; Nang ChanYeema (New York, USA Random House Inc., 1999)
Recounts how the Cherokees, after fighting to keep their land in the nineteenth century, were forced to leave and travel 1200 miles to a new settlement in Oklahoma, a terrible journey known as the Trail of Tears.
Keywords: Level Books